2001
DOI: 10.1063/1.1338968
|View full text |Cite
|
Sign up to set email alerts
|

Thermal microcrack distribution control in GaN layers on Si substrates by lateral confined epitaxy

Abstract: GaN epitaxial layers grown uniformly on Si substrates suffer from randomly distributed thermal cracks. The growth on prepatterned Si substrates is demonstrated as an efficient way to control the geometrical distribution of the thermal cracks. In order to study this effect and to find the maximum crack-free lateral dimension of a GaN patterned unit on Si, a simple procedure termed lateral confined epitaxy (LCE) was developed. This procedure confines the growth of GaN to separate mesas of Si, which are defined o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
4
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 7 publications
1
55
4
1
Order By: Relevance
“…2b. Cracks in GaN on Si are formed as a result of a large biaxial tensile stress [1], the origin of which is the large difference in the thermal expansion coefficients of GaN and Si(111). Recently, Amano et al [2] and Han et al [3] reported that an LT-AlN IL is effective in preventing further accumulation of the tensile stress in subsequent GaN overlayers, thereby suppressing the formation of cracks in GaN and AlGaN layers, where all layers were grown on (0001) sapphire substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b. Cracks in GaN on Si are formed as a result of a large biaxial tensile stress [1], the origin of which is the large difference in the thermal expansion coefficients of GaN and Si(111). Recently, Amano et al [2] and Han et al [3] reported that an LT-AlN IL is effective in preventing further accumulation of the tensile stress in subsequent GaN overlayers, thereby suppressing the formation of cracks in GaN and AlGaN layers, where all layers were grown on (0001) sapphire substrates.…”
Section: Methodsmentioning
confidence: 99%
“…However, the large differences in intrinsic material properties between GaN and Si(111) substrates such as the large degree of lattice mismatch (~17%), large differences in the thermal expansion coefficients (~37%), and their polar/nonpolor properties, give rise to the generation of extensive defects and, in particular, to the formation of dense microcracks along {1100} in GaN layers. It has been reported that cracks act as nonradiative and scattering centers in light propagation and electron transport, thus resisting in-plane electrical current, and producing shortcuts in vertical currents [1]. Therefore, it should be noted that a reduction in the density of cracks is needed to achieve acceptable device performance and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Because the lattice mismatch between GaN and Silicon substrate is larger than that of GaN and sapphire, the critical thickness for GaN on silicon is about 1-2 µm. Recently, some papers showed that it's feasible to obtain crack-free GaN islands on silicon substrate by using selective area growth method with metal organic vapour phase epitaxy (MOVPE) technology [7,8]. In those previous studies, the rectangular or hexagonal GaN islands were naturally grown on Si wafers, depending on their orientations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth of GaN on silicon substrate requires to develop complex buffer layers in order to avoid the apparition of cracks and to obtain high quality layers [1,2]. Another way to achieve uncracked and high quality layers is to use mesa patterned Si substrates [3,4]. In this case, strain in GaN layers is relaxed at mesa edges.…”
mentioning
confidence: 99%